Stock connectivity patterns and indications of sub-stock component structuring of cod in the Sound in the western Baltic Sea - Lundgreen, Regitze B.C.; Nielsen, Anders; van Deurs, Mikael; Olesen, Hans Jakob; Mion, Monica; Haase, Stefanie; Casini, Michele; Krumme, Uwe; Hüssy, Karin (Fisheries Research, 2023)
Sustainable management of fish stocks requires knowledge of stock structure and connectivity between spawning and feeding habitats. Cod in the Sound in the western Baltic Sea are an example of a stock component with complex connectivity patterns. Currently cod in this area are managed as part of the western Baltic cod stock, while several studies suggest potential connectivity with the neighbouring stock in Kattegat. Here we assess the degree of ecological connectivity of cod in the Sound with the neighbouring areas using historical tagging data from 1957 to 1987, and contemporary growth data from trawl surveys collected between 2007 and 2021. Furthermore, data from cod tagged outside of the Sound between 1960 and 2018 and recaptured in the Sound was used to examine immigration from outside areas. The ecological connectivity between the Sound and Kattegat appeared to be considerable, primarily during the spawning season. Furthermore, cod tagged in the northern Sound were most likely to be recaptured in Kattegat while cod tagged in the southern part of the Sound were mainly recaptured in the Sound. Only 40 out of 16,789 tagged cod released outside of the Sound were eventually recaptured inside the Sound. Overall, these results highlight the need for further examination into the current stock structure of cod in the western Baltic and adjacent areas.